2014
DOI: 10.1016/j.cub.2014.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Modulation of Intrinsic Functional Connectivity

Abstract: Serotonin functions as an essential neuromodulator that serves a multitude of roles, most prominently balancing mood. Serotonergic challenge has been observed to reduce intrinsic functional connectivity in brain regions implicated in mood regulation. However, the full scope of serotonergic action on functional connectivity in the human brain has not been explored. Here, we show evidence that a single dose of a serotonin reuptake inhibitor dramatically alters functional connectivity throughout the whole brain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
2

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 43 publications
5
72
2
Order By: Relevance
“…In our study, both agents altered resting state functional connectivity within our time frame of measurements. The results of our study replicate the finding that SSRIs can have an immediate and widespread diminishing impact on interactions of the healthy neural system [Klaassens et al, 2015; Murphy et al, 2009; Schaefer et al, 2014]. In conjunction with other SSRIs, citalopram had clear neuroendocrine effects [Seifritz et al, 1996], but did not induce cognitive or subjective changes as measured with the NeuroCart ® battery.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In our study, both agents altered resting state functional connectivity within our time frame of measurements. The results of our study replicate the finding that SSRIs can have an immediate and widespread diminishing impact on interactions of the healthy neural system [Klaassens et al, 2015; Murphy et al, 2009; Schaefer et al, 2014]. In conjunction with other SSRIs, citalopram had clear neuroendocrine effects [Seifritz et al, 1996], but did not induce cognitive or subjective changes as measured with the NeuroCart ® battery.…”
Section: Discussionsupporting
confidence: 85%
“…In congruence with both task‐related [Bruhl and Herwig, 2009; Murphy et al, 2009] and resting‐state fMRI paradigms with SSRIs [Klaassens et al, 2015; Schaefer et al, 2014], citalopram rapidly lowered connectivity in several cortical and subcortical regions. This is consistent with the numerous afferent and efferent serotonergic fibers originating from the brain stem's raphe nuclei [Baumgarten and Grozdanovic, 1995].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Negative phototactic behaviour of adult females decreased from 1 ng/L to 1 g/L of fluoxetine, from 0.01 to 1 g/L of carbamazepine and from 0.1 to 1 g/L of diazepam Despite that D. magna juveniles had lower negative phototactic behaviour, they responded similarly to the tested chemicals than adults. There is reported evidence showing that antidepressant action of fluoxetine in humans occurs after long exposures of about a month (Pérez et al, 2001), but recent studies indicated that effects of antidepressants can be detected within hours when more sensitive responses are measured (Schaefer et al, 2014). This is not the case for carbamazepine or diazepam that act shortly after being ingested (Besser, 1967;Post, 1988).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, we argue the potential effect of anesthetic agents was removed by contrasting the saline and ketamine treatments in the same group subjects and the thresholds for network construction were applied uniformly to each subject in both conditions. However, overinterpretation of the present findings from healthy subjects should be kept in mind (49,(64)(65)(66) until monkey models of mood disorders, such as depression and anxiety, have been developed (30) and used under the same experimental protocol. It was reported previously that schizophrenia-like symptoms can be induced by acute ketamine administration (67), although after a delay period (, 5 hours), the psychotomimetic effects do not last long in monkeys (32).…”
Section: Regional Regulation Of Small-world Networkmentioning
confidence: 95%